Culture and human capital investments: evidence of an unconditional cash transfer program in Bolivia - Monica Yanez-Pagans (Institute for the Study of Labor (IZA), 2008)
This paper uses a policy quasi-experiment created by the introduction of an old-age unconditional cash transfer program in Bolivia to study the intra-household income allocation process towards children's educational expenditure by ethnicity and gender of the recipient. Taking advantage of a sharp discontinuity created by the program assignment mechanism, I investigate the heterogeneity in the patterns of allocation within indigenous, multiethnic, and non-indigenous families, conditional on having one elder and one school-age child living in the household. I find that cultural factors (proxied by ethnicity) count in the decision making process of human capital investments. In particular, the allocation of resources within indigenous families follows rules closely related to patriarchal family structures (in which women have limited decision-making power) and is consistent with unitary, dictatorial, and common preferences theoretical household models. Conversely, non-indigenous families follow decision rules more closely related to collective and bargaining behavior models.
urn:nbn:de:101:1-2008092927
Keywords: H55; 330; Bolivia; culture; Bolivida; educational expenditure; Sozialhilfe; Alte Menschen; Bildungsinvestition; Kinder; Familiensoziologie; Ethnische Gruppe; Indigene Völker; Bolivien